(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:Reading books complain of weakness despite the renewal brought about by primary education in Iraq, and this weakness lies in the linguistic content of reading books, and this did not shed light on the problems in reading books (Samaa, 2013: 20) because of the scientific development that has taken place, the understanding of the minds of children and students has changed, Our education in Iraqi primary schools is still based on memorization and indoctrination, and interest in future sciences and dealing with current changes exists in theory but has nothing to do with reality. (Zayer and Iman: 2010: 78) The researcher believes that the problem of the weakness of reading books in primary education in Iraq is a cultural and intellectual problem, because its impact extends to the core of our lives, which encircles education from every aspect. The researcher noticed this problem while reading the reading books in the stage Elementary, as these books are devoid of the desired goals to be achieved in the books, in addition to providing the learner with the necessary skills for self-learning, i. Thinking skills and these skills develop the goals of the learning process and set realistic goals for each learner so that each learner finds the goals of the learning process educational goals that suit his needs and abilities and increases strong motivation for learners by providing diversity in educational materials, activities and goals. These skills will not be achieved, unless we overcome the learning difficulties that It is a type of manifestation of an individual’s academic inability to learn language and its branches such as reading, writing and spelling, which are due to mental reasons. Emotional or sensory and individuals (Nabhan: 2008-81)Keywords: thinking, visual skills, reading.